Choices choices: regulation of precursor differentiation during enteric nervous system development. Issue 7 (1st May 2013) - Harrison, C.; Shepherd, I. T.
Abstract Background The enteric nervous system (ENS) is the largest subdivision of the peripheral nervous system and forms a complex circuit of neurons and glia that controls the function of the gastrointestinal (GI) tract. Within this circuit, there are multiple subtypes of neurons and glia. Appropriate differentiation of these various cell subtypes is vital for normal ENS and GI function. Studies of the pediatric disorder Hirschprung's Disease (HSCR) have provided a number of important insights into the mechanisms and molecules involved in ENS development; however, there are numerous other GI disorders that potentially may result from defects in development/differentiation of only a subset of ENS neurons or glia. Purpose Our understanding of the mechanisms and molecules involved in enteric nervous system differentiation is far from complete. Critically, it remains unclear at what point the fates of enteric neural crest cells (ENCCs) become committed to a specific subtype cell fate and how these cell fate choices are made. We will review our current understanding of ENS differentiation and highlight key questions that need to be addressed to gain a more complete understanding of this biological process.